The Readymade Garments (RMG) sector of Bangladesh : exploring sustainability dimensions - Amin, Khan Md. Nurul (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of MA in Governance and Development, 2015.